Adaptation to poverty in long-run panel data - Andrew E. Clark; Conchita D'Ambrosio; Simone Ghislandi (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We consider the link between poverty and subjective well-being, and focus in particular on potential adaptation to poverty. We use panel data on almost 45,800 individuals living in Germany from 1992 to 2011 to show first that life satisfaction falls with both the incidence and intensity of contemporaneous poverty. We then reveal that there is little evidence of adaptation within a poverty spell: poverty starts bad and stays bad in terms of subjective well-being. We cannot identify any causes of poverty entry which are unambiguously associated with adaptation to poverty.
Keywords: I31; D60; 330; income; poverty; subjective well-being; adaptation; SOEP